Profile Of Pediatric Malignancy: A Three-Year Study - Bhalodia, Jignasa N; Patel , Mandakini M (National Journal of Community Medicine, 2011)
The objective of this study was to find out the profile of childhood cancers in South Gujarat region, during November 2002 to October 2005. Between November 2002 to October 2005 data was analyzed for the malignancies occurring in the age group 0-14 years. Data was categorized according to incidence of pediatric malignancies in different age groups, sex and types of tumors. All the children below 15 years with confirmed diagnosis of cancer by means of histological or cytological examinations were included in this study. Total 2150 patients were diagnosed as having malignancies in our hospital out of which 43 were pediatric tumors. Overall incidence of pediatric tumor was 2%. The peak incidence of pediatric tumors (44.18%) was found in children below five years of age. Males were affected more than females. Among hematological malignancies most common was acute lymphoblastic leukemia. The pattern of childhood tumors shows wide variation among the age groups. Acute lymphoblastic leukemia, lymphoma and CNS tumors are most common tumors in this age group.